Alzheimer's disease in one monozygotic twin. Issue 5 (October 1972) - Hunter, Richard; Dayan, A. D.; Wilson, John
Abstract : A woman of 64 died after an illness lasting 15 years and characterized by a progressive amnesic syndrome followed by global dementia. The brain showed changes typical of Alzheimer's disease. Her monozygotic twin sister was clinically not affected and died two years later of carcinoma. This is the second report of monozygotic twin sisters apparently discordant for presenile dementia of Alzheimer type.